Effect of different soluble salt ions on deformation of desulfurization gypsum in high humidity environment: a statistically designed experimental analysis method. (1st April 2023) - Zhou, Shuang-xi; Liu, Chao-qun; Dai, Li; Zhang, You-hua; Zhu, Ze-wen; Mao, Lin; Ding, Yang; Han, Zhen; Dong, Jiang-liang; She, An-ming; Wei, Yong-qi
Abstract: In response to the green energy-saving goal of carbon neutralization and carbon peak, the research and development of green building materials have become a key research direction. Desulfurization gypsum is widely used in building materials because of its good energy saving, but it cannot be used in high humidity areas because of its highly soluble salt. Based on this reason, this paper uses statistically designed experiments (SDE) to design the experiments on the influence of four common soluble salt ions N a +, M g 2 +, C l − and K + on the sagging deformation of desulfurization gypsum, and studies the significance of their influence by SDE experimental analysis method. The results show that: (1) in the environment of a single salt solution, K + ion, M g 2 + ion, N a + ion, and C l − ion will cause sagging deformation of desulfurization gypsum, and their values are 0.432 mm, 1.933 mm, 0.942 mm, and 0.940 mm respectively. It can be seen that the effect of the M g 2 + ion is the most significant. (2) In the environment of composite salt solution, K + ions will inhibit the sagging deformation of desulfurization gypsum. Specifically, in the compound salt solution environment of K + + M g 2 + and K + + N a +, the deformation values are 0.605 mm and 0.596 mm respectively.